Awareness, acceptance and practice of plastic ban legislation among residents of an urban area in Kanchipuram district, Tamil Nadu: a cross sectional study - P., Sujitha; N. B., Swetha; S., Gopalakrishnan (International Journal Of Community Medicine And Public Health, 2019)
Background: Convenience of plastic use pays a high price by negatively affecting health and environment. As nationwide ban on use of plastic carry bags failed, statewide ban was imposed in Tamil Nadu from 1st January 2019. This study was planned with the objective of determining the awareness, acceptance and practice of plastic ban legislation among residents in urban population in Kancheepuram district, Tamil Nadu. Methods: This community based cross sectional study was carried out with a sample size of 250 using systematic random sampling method. Data was collected using structured questionnaire and further analysis was done with SPSS Version 25 Software. Results: About 94% respondents were aware of legislation and 76% had a positive attitude towards the ban. About 52% participants continued using plastic bags despite the ban. Common source of knowledge about the ban was mass media (42%). About 80% were aware of the negative effects of plastic use and 70% were aware that plastics are non-bio-degradable. Statistically significant association was found between various socio demographic factors with the use of plastic bags. Alternate eco-friendly bags usage was found among 48% of respondents. Conclusions: Good awareness level about the ill effects of plastic use and its ban was observed but the level of implementation in their daily life was poor. Even after the preparatory period of six months given to get accustomed to eco-friendly alternatives, the use of plastic bags still remains rampant. IEC activities need to be intensified to bring about changes in the attitude and practice of plastic use.